2020
DOI: 10.3390/ijms22010320
|View full text |Cite
|
Sign up to set email alerts
|

The Signaling Pathways Involved in the Anticonvulsive Effects of the Adenosine A1 Receptor

Abstract: Adenosine acts as an endogenous anticonvulsant and seizure terminator in the brain. Many of its anticonvulsive effects are mediated through the activation of the adenosine A1 receptor, a G protein-coupled receptor with a wide array of targets. Activating A1 receptors is an effective approach to suppress seizures. This review gives an overview of the neuronal targets of the adenosine A1 receptor focusing in particular on signaling pathways resulting in neuronal inhibition. These include direct interactions of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 195 publications
(243 reference statements)
0
7
0
Order By: Relevance
“…The transcription factor NF kB regulates the expression of anti apoptotic proteins [14]. TRADD mediated degradation of the NF kB IkB complex allows the NF kB p65 isoform to translocate into the nucleus, where it regulates the transcription of a wide range of genes responsible for the synthesis of proteins, such as Bcl 2, IL 6, IL 8, and VEGF, which are involved in cell sur vival [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor NF kB regulates the expression of anti apoptotic proteins [14]. TRADD mediated degradation of the NF kB IkB complex allows the NF kB p65 isoform to translocate into the nucleus, where it regulates the transcription of a wide range of genes responsible for the synthesis of proteins, such as Bcl 2, IL 6, IL 8, and VEGF, which are involved in cell sur vival [25].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported the association of the nuclear factor NF kB, a master regulator of the inflammatory response, with epilepsy in ani mals [14]. NF kB consists of two subunits, and its most common form is the p65/p50 heterodimer, which typically exists in the cytoplasm in a form inhibited by the IkB protein.…”
Section: Introductionmentioning
confidence: 99%
“…In human temporal lobe epilepsy, the density of the A1Rs is increased [ 29 ] or decreased in the temporal neocortical region of the brain [ 21 ]. In animal models, however, the A1R density is decreased in rat hippocampal pyramidal neurons [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presynaptically, voltage-gated Ca 2+ channels are inhibited, resulting in reduced neurotransmitter release. Postsynaptically, G protein-mediated inwardly rectifying potassium channels are activated, resulting in membrane hyperpolarization [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%